(untitled) (Intent Research Scientific Journal, 2023)
Childhood hearing impairment of at least an average weight of two-way affects 1 in every 750 children in Western countries. Differences in these results depend not only on hearing loss and hearing loss with hearing apparatus or cochlear implants, but also on a variety of factors, such as additional disability, IQ, parental resources and educational conditions.